Effectiveness and safety of generic version of abacavir/lamivudine and efavirenz in treatment naïve HIV-infected patients: a nonrandomized, open-label, phase IV study in Cali-Colombia, 2011-2012 (2016)
ABSTRACT: Background: Generic drug policies are often associated with concerns about the quality and effectiveness of these products. Phase IV clinical trials may be a suitable design to assess the effectiveness and safety of generic drugs. The objective of this study was to describe the effectiveness and the safety of the generic abacavir/lamivudine and efavirenz in treatment-naïve HIV-infected patients. Methods: A monocentric, nonrandomized, open-label, phase IV study in treatment naïve HIV-infected patients 18 years or older with indication to receive abacavir/lamivudine and efavirenz were recruited from a program that provides comprehensive outpatient consultation and continuing care. The primary end-point was to achieve viral load <40 copies/mL at 12 months after baseline to assess effectiveness. Secondary end-point of the study were 1) to asses increasing in T-CD4 lymphocytes levels as accompaniment to asses effectiveness, and 2) to assess both gastrointestinal, skin, and central nervous system symptoms, and lipid profile, cardiovascular risk, renal, and hepatic function as safety profile. Data were determined at baseline, 3, 6, and 12 months. Close clinical monitoring and pharmaceutical care were used for data collection. Wilcoxon matched-pairs signed-rank test was used to compare proportions or medians. Results: Sixty patients were invited to participate in the study; 42 were enrolled and 33 completed the follow-up. Of the nine patients excluded from the study, only one was withdrawn due to adverse events. At 12 months, 31 of 42 patients (73.8 % in intention-to-treat analysis) achieved a viral load of HIV1 RNA <40 copies/mL. There was a significant increase (172 cells/mm3) in the median for CD4 T lymphocyte count. The adverse events were mild and met the safety profile for this antiretroviral regimen, mainly of central nervous system symptoms, skin rash, lipid abnormalities, and an increase of 2 % in the median of the percentage of cardiovascular risk. Conclusions: The clinical outcomes of generic version of abacavir/lamivudine and efavirenz in HIV treatment naïve patients showed the expected safety and effectiveness profile of proprietary ARV drugs